Euro area CDS spreads in the crisis: The role of open market operations and contagion - GERLACH, PETRA (ESRI)
This paper studies euro area CDS spreads during the financial crisis. We examine the impact of the crisis on both commercial banks and sovereigns, and focus on two questions. First, have the ECB?s open market operations reduced market stress? It seems that large repo volumes, especially if credited to banks the same day, helped initially, and that the announcement of the Securities Market Programme also calmed markets. Asset purchase volumes do not seem to matter directly. Second, was there contagion among and between banks and sovereigns? We find evidence for both. Interestingly, sovereign CDS spreads appear immune after April 2010. We argue that this might reflect the ECB?s efforts to stop contagion during the euro crisis.
PUBLISHED
Keywords: Economics